Applying mobile eye tracking to measure real-time engagement and enhance informal learning at environmental exhibits - Lohani, Monika; Zummo, Lynne; Roberts, Alec G.; Blodgett, Ginger R. (Frontiers in Psychology, 2025)
Mobile eye-tracking is a valuable method that holds significant potential for understanding informal learning in applied environmental science settings, yet it remains underutilized. In this paper, we explore the benefits of adopting this technology to objectively assess engagement in real-time, which can inform the design and advancement of informal learning through environmental science exhibits. In addition, mobile eye-tracking offers technology to conduct state-of-the-art research in applied museum settings. Using a climate change exhibits as an example, we illustrate ways to leverage this technology to improve exhibit design and deepen our understanding of visual engagement and informal learning. Finally, we address the challenges and areas for growth in applied eye-tracking technology. Overall, we present what this cutting-edge methodology can offer to enhance engagement and learning through environmental exhibits.